Pengaruh Pengetahuan, Motivasi, Modal Investasi Minimal, dan Return Terhadap Minat Investasi Mahasiswa di Pasar Modal Syariah - Raja Fatahilah Khafi; Deny Yudiantoro (Universitas Batanghari, 2022)
This study aims to determine the effect of knowledge, motivation, minimal investment capital, and return on investment interest of Islamic capital market students on Islamic Financial Management students at PTKI in East Java. The approach used in this research is to use a quantitative survey technique. Sources of data used are primary data with the number of respondents as many as 96 students with the data collection method using a questionnaire. Then the data is processed using SPSS 25 to test the validity, reliability, classical assumption test, and multiple linear regression. The results obtained from this study are the knowledge variable has no effect on student investment interest in the Islamic capital market. While the variables of motivation, minimal investment capital, and return have an effect on student investment interest in the Islamic capital market.